AAV Vectors Vaccines Against Infectious Diseases - Nieto, Karen; Salvetti, Anna (Frontiers in Immunology, 2014)
Since their discovery as a tool for gene transfer, vectors derived from the adeno-associated virus (AAV) have been used for gene therapy applications and attracted scientist to this field for their exceptional properties of efficiency of in vivo gene transfer and the level and duration of transgene expression. For many years, AAVs have been considered as low immunogenic vectors due to their ability to induce long-term expression of non-self-proteins in contrast to what has been observed with other viral vectors, such as adenovirus, for which strong immune responses against the same transgene products were documented. The perceived low immunogenicity likely explains why the use of AAV vectors for vaccination was not seriously considered before the early 2000s. Indeed, while analyses conducted using a variety of transgenes and animal species slowly changed the vision of immunological properties of AAVs, an increasing number of studies were also performed in the field of vaccination. Even if the comparison with other modes of vaccination was not systemically performed, the analyses conducted so far in the field of active immunotherapy strongly suggest that AAVs possess some interesting features to be used as tools to produce an efficient and sustained antibody response. In addition, recent studies also highlighted the potential of AAVs for passive immunotherapy. This review summarizes the main studies conducted to evaluate the potential of AAV vectors for vaccination against infectious agents and discusses their advantages and drawbacks. Altogether, the variety of studies conducted in this field contributes to the understanding of the immunological properties of this versatile virus and to the definition of its possible future applications.